309 HORMONAL CONTROL OF AQUAPORIN 2 REQUIRES ADVANCED TUBULAR STRUCTURES IN AVIAN KIDNEYS. (1st January 2006) - Lau, K.; Yang, Y.; Cook, G.; Wyatt, R.; Nishimura, H.
Abstract : Purpose: To determine the effects of water deprivation and vasotocin (AVT, avian ADH) treatment on the regulation of quail aquaporin 2 (qAQP2) mRNA expressions in looped (advanced) and loopless (primitive) nephrons of adult quail kidneys. Introduction: Birds and mammals are the only vertebrates that can concentrate urine. Avian kidneys contain both primitive loopless (mainly found in the cortical regions) and more advanced looped (found in the medullary regions) nephrons. Only the looped nephrons can produce hyperosmolar urine. We have previously identified an AQP2 homologue in quail kidney with ˜77% homology to rat AQP2. Immunoreactive qAQP2 is expressed on the apical side of the collecting ducts (CD) in both cortical and medullary regions and is enhanced by dehydration and AVT only in medullary CDs, suggesting that the regulatory role of AVT in water transport may have evolved in looped nephrons. Methods: Sexually matured quails at 6 weeks old were examined in 4 groups (n = 10-12) as follows: (1) normal hydration (C); (2) vasotocin treated (V) (50 ng/kg/d, by subcutaneous mini-pump, 72 h); (3) water deprived (WD) for 72 h; (4) WD plus V as above. RNA in both cortical and medullary regions (normalized with 18S) was measured by real-time PCR after reverse transcription. Results: In all groups, qAQP2 mRNA levels are higher (3.6 to 4.7 times) in the medulla than cortex. Differences in mean (6 SE) qAQP2 mRNA quantities in cortex among the groups are not significant; C (0.19 6 0.06), V (0.16 6 0.05), WD (0.37 6 0.05), and WD plus V (0.34 6 0.11). Mean qAQP2 mRNA levels are significantly higher (p < .01) in the medulla from WD (1.09 6 0.10) and WD plus V (1.21 6 0.19) than C (0.54 6 0.10) and V (0.54 6 0.06). Conclusions: The results suggest that qAQP2 expressions are higher in medullary regions with the looped nephrons. Advanced tubular structures may be required for water control by ADH-axis via AQP2 expressions in avian kidneys.